OP0070 The role of individual and country-level socio-economic factors in work participation in patients with spondyloarthritis across 22 countries worldwide: results from the comospa study. (15th June 2017) - Manica, S Rodrigues; Sepriano, A; Ramiro, S; Pimentel-Santos, FM; Putrik, P; Nikiphorou, E; Moltό, A; Dougados, M; Heijde, D van der; Landewé, R; Bosch, F Van den; Boonen, A
Abstract : Background: Spondyloarthritis (SpA) carries substantial financial costs, including direct costs (use of medical services and treatments) and indirect costs (loss of work productivity). While disease related factors have been repeatedly shown to be associated with work outcomes, information on the role of educational attainment and the economic wealth of the patients' country of residence is scarce. Objectives: To explore the role of individual and country level socio-economic (SE) factors on employment, absenteeism and presenteeism across 22 countries. Methods: Patients with a clinical diagnosis of SpA, fulfilling the ASAS SpA criteria and in working age (≤65 years old) from COMOSPA were included. Outcomes explored were employment-status, absenteeism and presenteeism according to the Work Productivity and Activity Impairment Specific Health Problem (WPAI-SHP) questionnaire. Absenteeism and presenteeism were assessed in employed patients. Multilevel logistic (for work status) and linear (for absenteeism and presenteeism) regression models with random intercept for country were constructed. Independent contribution of individual (education) and country level socio-economic factors (country healthcare expenditures and gross domestic product (GDP) (all low vs medium/high tertiles) were assessed in models adjusted for clinical factors. Results: In total 3, 114 patients from 22 countries were included (mean (SD) age 40.9 (11.8) years; 66% males; and 63% employed). Of these, 89% had axial SpA and 11% a peripheral SpA. Unadjusted employment rates ranged from 28% (Colombia) to 83% (Canada). After adjustment for relevant socio-demographic and clinical variables, differences between countries in work status persisted (Figure). High healthcare expenditures were associated with higher employment (OR=2.42; 95% CI=1.53;3.81) and lower presenteeism (β=-4.53;CI=-8.90;-0.17). Similarly, higher GDP was associated with higher employment (OR=1.70; 95% CI=1.02;2.83), and in the same direction with presenteeism but without reaching statistical significance (β=-3.42;CI=-13.07;6.23). No significant association between any country SE indicators and absenteeism was found. At individual level, higher education was positively associated with employment-status, presenteeism and absenteeism. Conclusions: Individual- and country-level SE factors affect work participation in SpA, and this varies significantly across countries. Better socio-economic welfare seems to support SpA patients to stay employed and productive. Disclosure of Interest: None declared